State of the research on solar activity impact on the radio waves propagation - Stancheva, Anushka; Petrov, Georgi; Tzvetkov, Plamen; Alexandrov, Angel; Benkova, Bilyana (Yearbook Telecommunications, 2015)
This publication reviews the current status and importance of solar activity influence on the radio waves propagation during different conditions. We analyze the worldwide trends and the state of scientific research in this direction as well as the networks for cooperation and exchange of information between stakeholders.